If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1/2(6x-4)=3x+2
We move all terms to the left:
1/2(6x-4)-(3x+2)=0
Domain of the equation: 2(6x-4)!=0We get rid of parentheses
x∈R
1/2(6x-4)-3x-2=0
We multiply all the terms by the denominator
-3x*2(6x-4)-2*2(6x-4)+1=0
Wy multiply elements
-6x^2(6-4x(6+1=0
| 3x+4(-4x-6)=119 | | 3x+4(-4x6)=119 | | 3/9p=9 | | -3(x+4)=-2x+1 | | (3/10)x-3x+(4/5)=(3/5) | | 4x+8x-57=38-7 | | x-(15x-6)=107 | | 6x+3(3x+22)=216 | | 517=83-x | | 5c=c | | 517=83-c | | 85-4x=75-3.5x | | -8(7x+31)=-976 | | x+6/5-x-3/7=12/7 | | 7x+3(4x/)=109 | | 162-12x=-20x-246 | | -1x+1(x-1)=2 | | 60=2/3x+x | | 5(x-9)=35-3x | | (3x+33)(2x-3)=180 | | 3(w-5)-8w=5 | | 0.5(6x-4)=3x+2 | | 2(2x)+x=17.5 | | 1(x-1)=x+2 | | (3x–1=-10) | | -8x+83=-x-176 | | 11b+20=40 | | 12+4n=–4 | | -30-5x=123 | | (x-5)2=x+1 | | -12m+4m=18-3 | | c÷2=14 |